One-Pot Synthesis of New 4,5,6,7-tetrahydro-3H-[1,2]dithiolo[3,4-b]pyridines Starting from N,N’-Diphenyldithiomalondiamide - Ekaterina A. Varzieva; Anna E. Sinotsko; Victor V. Dotsenko; Nicolai A. Aksenov (Chemistry Proceedings)
Active methylene compounds such as thioamides are widely used in the organic chemistry for the construction of a variety of heterocyclic systems, such as thieno[2,3-b]pyridines, 1,2,4-dithiazoles, isothiazoles, 1,2,3-thiadiazoles, etc. N,N′-Diphenyldithiomalondiamide (dithiomalondianilide) as a compound with methylene active group is also of interest as a starting reagent for the synthesis of new N,S-containing heterocycles with potential pharmacological application. However, the reactions of dithiomalondianilide are poorly studied. In the present study, we report the synthesis of new 4,5,6,7-tetrahydro[1,2]dithiolo[3,4-b]dithiolopyridine-5-carboxamides through the reaction of dithiomalondianilide with 3-aryl-2-cyanoacrylamides. The products were characterized using FTIR and NMR spectroscopy as well as X-ray analysis.